Trends in European language education policy on teacher education: Teaching foreign languages to young learners - Komorowska, Hanna; Krajka, Jaroslaw (Glottodidactica, 2024)
Contemporary language education to young learners is seeing an increased focus on individual variation, due to students’ special educational needs and the diversity of contexts in which instruction takes place. This leads to the increased creativity of teachers and the emergence of innovative practices in various areas of teaching languages to children. On the other hand, due to globalization and international cooperation, language teaching experiences a degree of standardization. One source of this may be the impact of European education policy. Due to such influential tools as the Common European Framework of Reference for Languages or the European Portfolio for Pre-Primary Educators, educational systems find it convenient and useful to apply some of these assumptions. Therefore, it is important to make an overview of trends in European education policy in reference to teaching young learners, to indicate what kind of support can be given to language instructors in their work with children. The research question posed in the paper is to what extent the most important European policy documents and tools prove relevant in the practice of young learner educators? The analysis indicates the viability of selected European policy tools, modifications of their use across the years and new forms of implementation in the social media era.